Distribution and movement of juvenile and sub‐adult Chinese sturgeon (Acipenser sinensis Gray, 1835) in the Three Gorges Reservoir and the adjacent upstream free‐flowing Yangtze River section: a re‐introduction trial. (12th November 2013) - Du, H.; Wang, C.Y.; Wei, Q.W.; Zhang, H.; Wu, J.M.; Li, L.
Summary The aim of this 2008–2012 study was to prove the hypothesis that the Three Gorges Reservoir (TGR) and the upper free‐flowing section can offer a habitat for restocking the Chinese sturgeon, Acipenser sinensis. Thus, 498 cultured A. sinensis (including 28 sub‐adults tagged with ultrasonic transmitters) were released into the TGR and the adjacent free‐flowing section of the Yangtze River. The distribution, movement and growth of the released fish were collected by acoustic telemetry and bycatch information. Results indicated that only three sub‐adults migrated upstream to the free‐flowing section where they remained for the three‐year observation (limited by the longevity of the transmitter battery). However, most sub‐adults migrated downstream after release, with a migration distance of 15–877 km as well as a tracking duration from 19 to 6063 h. The downstream traveling speed in the free‐flowing section (mean = 3.70 km h−1, range = 1.51–8.25 km h−1) was significantly faster than that in the reservoir section (mean = 1.05 km h−1, range = 0.12–1.82 km h−1; p < 0.05). Only three sub‐adults migrated to within 3 km of Three Gorges Dam (TGD) and stayed in the reservoir. Sub‐adults stayed obviously deeper within the reservoir (mean = 11.47 m) than in the free‐flowing section (mean = 3.63 m; p < 0.05). Juveniles were recaptured from 45–810 km downstream their release sites with a mean traveling speed of 1.05 km h−1 (range = 0.13–1.82 km h−1), lower than that of the sub‐adults released in the free‐flowing section. Twelve percent of juveniles released in one of the tributaries of the Yangtze River found the entrance and migrated downstream to the reservoir within the first 30 days. Average body weight of the recaptured juveniles increased by 10.3% (range = 2.3%–15.3%) and some crustaceans (e.g. river shrimp) were found in the stomach and gut of two juveniles. The results demonstrate that the TGR and its adjacent upstream free‐flowing Yangtze River section can serve as reintroduction sites to support a certain quantity of Chinese sturgeon to remain and mature there.